On generalized double almost statistical convergence of weight g - Savaş, E. (Carpathian Mathematical Publications, 2022)
The purpose of this paper is to introduce the concept of λ-double almost statistical convergence of weight g, which emerges naturally from the concept of the double almost convergence and λ-statistical convergence. Some interesting inclusion relations have been considered.